Virtual Screening, Toxicity Evaluation and Pharmacokinetics of Erythrina Alkaloids as Acetylcholinesterase Inhibitor Candidates from Natural Products - Permana A; Akili AWR; Hardianto A; Latip JB; Sulaeman AP; Herlina T (Advances and Applications in Bioinformatics and Chemistry)
Afri Permana,1 Abd Wahid Rizaldi Akili,1 Ari Hardianto,1 Jalifah Binti Latip,2 Allyn Pramudya Sulaeman,1 Tati Herlina1 1Department of Chemistry, Faculty of Mathematics and Natural Science, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Department of Chemical Sciences, Faculty of Science and Technology, Universiti Kebangsaan Malaysia (UKM), Selangor, MalaysiaCorrespondence: Tati Herlina, Email tati.herlina@unpad.ac.idPurpose: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder with limited treatment options, necessitating the development of safer and more effective therapies. The potential of alkaloids derived from the genus Erythrina as acetylcholinesterase (AChE) inhibitors is being investigated to enhance acetylcholine levels in the brain, which is crucial for the treatment of AD. The objective of this study is to identify Erythrina alkaloids with strong inhibitory capacity against AChE and favorable pharmacokinetic profiles.Materials and Methods: A multi-step computational approach was employed, beginning with the virtual screening of 143 Erythrina alkaloid structures using molecular docking against the human AChE crystal structure. The binding affinities were compared with the known AChE inhibitor, galantamine. The top alkaloid, 8-oxoerymelanthine ( 128), was subjected to further analysis through molecular dynamics simulations, with the objective of evaluating its stability and interactions. In silico ADMET predictions were conducted to assess the pharmacokinetic properties. The applicability of Lipinski’s Rule of Five was applied to evaluate oral drug-likeness.Results: 8-Oxoerymelanthine ( 128) exhibited the highest binding affinity and remarkable stability in molecular dynamics simulations. The toxicity predictions indicated a low risk of mutagenicity, hepatotoxicity, and cardiotoxicity. Pharmacokinetic assessments indicated good absorption, moderate blood-brain barrier penetration, and favorable metabolic and excretion profiles, supporting its potential as an orally active drug candidate.Conclusion: 8-Oxoerythmelanthine ( 128) exhibits strong potential as an AChE inhibitor with a favorable balance of efficacy, safety, and pharmacokinetic properties. These results warrant further investigation in preclinical and clinical studies to validate its therapeutic potential and safety for Alzheimer’s disease treatment.Keywords: Erythrina alkaloid, pharmacokinetics, In silico, acetylcholinesterase inhibitors, virtual screening